Gesture Controlling Robotic Car with Hand by Using Flex Sensors - Md. Muntasir Rahman Plaban, Most. Mahzuba Islam, Md.Toha Anas, Md.Mostofa Abid (Mathematical Statistician and Engineering Applications, 2023)
The main theme and aims of the work are to originate a very simple usable and self-intellect design for a car that is implemented in versatile areas. Truly we propose a real-time hand gesture that will reduce the scattering in driving mode. In our daily life, we are getting attached more to machines and their communication system as it is confirmed that more proficiency and interaction is perfect. We represent our research on an automated smart car for physically unfit people in this paper. So, keeping all the facts and issues in mind, proposed and designed in that way a hand gesture robotic car, controlled by two flex sensors with six commands, which is more efficient, accurate and cost-effective than before. In addition, even an individual person could operate with two fingers and real-time hand gesture recognition. The most attractive and finest part of the work is to assemble a lot of devices in them: a 3-axis accelerometer (MPU6050), flexible flex sensor with ATmega328P microcontroller. Furthermore, a little bit of AI technology has been added by sound waves.